The Profile of Anticancer Activities of Sambiloto Extract (Andrographis paniculata Nees) from Several Locations in East Java - Roihatul Mutiah; Fina Luthfiana; Arief Suryadinata; Wirda Anggraini; Anik Listiyana (Journal of Food and Pharmaceutical Sciences, 2020)
Sambiloto (Andrographis paniculata Nees) contains andrographolid compound which has potential as an anticancer. The difference of growth location has affected the distinction of metabolite content. This study aims to determine the profile of anticancer activities of A. paniculata extract from several locations in East Java. The extracts from several locations were tested for activity on T47D cancer cell using MTT assay method. Thus, the result of this study describes that A. paniculata extract from several different locations does not provide significantly different anticancer activities with the amount of (p>0.05). The extracts which have moderate anticancer activity were A. paniculata extracts from Selopuro Subdistrict Blitar Regency, Singosari Subdistrict Malang Regency, Lowokwaru Subdistrict Malang City, Klojen Subdistrict Malang City, Purwodadi Subdistrict Pasuruan Regency, Purwosari Subdistrict Pasuruan Regency, and Pandaan Subdistrict Pasuruan Regency